Legal Protection For Contractors With Contract Providers For Procurement Of Goods / Services Due To Covid 19 (Case Study Of PT. Dharma Agung Wijaya) - Dedek Maulana; Nurhayati Nurhayati; Ruslan Ruslan (Legalpreneur Journal, 2022)
The covid 19 pandemic influenced the implementation of the agreement experienced between PT. Indo Hutama Jaya and PT. Dharma Agung Wijaya where work was hampereddue to regulations during the pandemic which required workers from outside the region tobe quarantined for 14 days and there was a decrease in economic capacity which affectedthe implementation of the agreement. Indo Hutama jaya?, How is the legal protection ocontractors with goods/services contractors in procurement agreements during the covid 19pandemic?. The research methods used are normative and empirical juridical research. Thenature of the research used in this study is descriptive analysis. Based on the results of thestudy, the conclusion in this study is that delays occur almost in every implementation andhave different problems, factors that cause delays in the implementation of contracts thatoccur in PT. Indo Hutama Jaya and PT. Dharma Agung Wijaya explained that both the Firstparty and the second party are exempt from liability for failure or delay in performing theiobligations under this contract, caused by things beyond the reasonable ability of the parties and not caused by negligence of the parties. Responsibility of the board of directorsfor the contractual relationship with the second party where the board of Directors is responsible for controlling and supervising the implementation of the contract inaccordance with the scope of work, cost, term and other provisions agreed.